Micromechanical modeling of the cement-bone interface: the effect of friction, morphology and material properties on the micromechanical response - Janssen, Dennis (2008)
In order to gain insight into the micro-mechanical behavior of the cement-bone interface, the effect of parametric variations of frictional, morphological and material properties on the mechanical response of the cement-bone interface were analyzed using a finite element approach. Finite element models of a cement-bone interface specimen were created from micro-computed tomography data of a physical specimen that was sectioned from an in vitro cemented total hip arthroplasty. In five models the friction coefficient was varied (μ= 0.0; 0.3; 0.7; 1.0 and 3.0), while in one model an ideally bonded interface was assumed. In two models cement interface gaps and an optimal cement penetration were simulated. Finally, the effect of bone cement stiffness variations was simulated (2.0 and 2.5 GPa, relative to the default 3.0 GPa). All models were loaded for a cycle of fully reversible tension-compression. From the simulated stress-displacement curves the interface deformation, stiffness and hysteresis were calculated. The results indicate that in the current model the mechanical properties of the cement-bone interface were caused by frictional phenomena at the shape-closed interlock rather than by adhesive properties of the cement. Our findings furthermore show that in our model maximizing cement penetration improved the micromechanical response of the cement-bone interface stiffness, while interface gaps had a detrimental effect. Relative to the frictional and morphological variations, variations in the cement stiffness had only a modest effect on the micromechanical behavior of the cement-bone interface. The current study provides information that may help to better understand the load transfer mechanisms taking place at the cement-bone interface.